Merancang Masa Depan : Perkembangan Peserta Didik Dalam Perspektif Pendidikan Abad 21 - Laili, Wahdania Rohmatul (Ibtida'iy : Jurnal Prodi PGMI, 2025)
The demands of 21st-century education present complex challenges and opportunities, necessitating pedagogical adjustments to adequately prepare students for future dynamics. This study aims to investigate how the principles of 21st-century education can be systematically applied to support the holistic development of students. A literature review method employing descriptive analysis was utilized to synthesize relevant theoretical and empirical studies on 21st-century educational practices. The results demonstrate that effective 21st-century education prioritizes the integration of new literacies, the cultivation of critical thinking skills, global collaboration competencies, and character education, all of which are essential for developing competent, adaptive, and resilient learners. This study underscores that strategic collaboration among educators, policymakers, and technological stakeholders is pivotal in designing relevant, contextualized, and future-oriented learning strategies. The findings offer theoretical and practical insights for enhancing educational practices in the digital era.